2017
DOI: 10.1371/journal.pone.0181621
|View full text |Cite
|
Sign up to set email alerts
|

Development of organic fertilizers from food market waste and urban gardening by composting in Ecuador

Abstract: Currently, the management of urban waste streams in developing countries is not optimized yet, and in many cases these wastes are disposed untreated in open dumps. This fact causes serious environmental and health problems due to the presence of contaminants and pathogens. Frequently, the use of specific low-cost strategies reduces the total amount of wastes. These strategies are mainly associated to the identification, separate collection and composting of specific organic waste streams, such as vegetable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
(76 reference statements)
0
17
0
4
Order By: Relevance
“…Particularly, tomato germination was the most affected by the NFCE, followed by watercress then chili pepper, the latter was negatively impacted by the extract (Table 4). This fact could be explained by the eventual presence of inhibiting substrates when used at high concentrations, especially phenolic compounds and lignin, as the main components in composted plant materials [38]. Indeed, the presence of phenolic compounds in vegetable wastes compost was reported, these are specific phytochemical antioxidants naturally present in practically all plant materials [42].…”
Section: Fermented Compost Extract' Effect On Seeds Germination and Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, tomato germination was the most affected by the NFCE, followed by watercress then chili pepper, the latter was negatively impacted by the extract (Table 4). This fact could be explained by the eventual presence of inhibiting substrates when used at high concentrations, especially phenolic compounds and lignin, as the main components in composted plant materials [38]. Indeed, the presence of phenolic compounds in vegetable wastes compost was reported, these are specific phytochemical antioxidants naturally present in practically all plant materials [42].…”
Section: Fermented Compost Extract' Effect On Seeds Germination and Gmentioning
confidence: 99%
“…The soft rot fungi:Chaetomium, Ceratocystis, and Kretzschmaria deusta can decompose cellulose but degrade lignin slowly and incompletely. Therefore, the regulation and consoil properties and availability of nutrients that would activate the microbial flora[26] [31][34] [38] [39][40]. In 2020, Voběrková et al[2] mentioned high enzymatic activities in FWC, when used alone or supplemented with biochar and sawdust such as deshydrogenases, proteases, β-D-glucosidases, phosphatases and arylsulphatases during 35 days of composts' maturation.…”
mentioning
confidence: 99%
“…Some studies reported that it is essential to reduce food loss and food waste for the question of food security [75]. This can be done by using the fruit and vegetable waste at a retail and consumer level (supermarkets and food markets) as substrates in bioprocesses [88] to produce organic fertilizers [89,90], as long as this waste is treated correctly to reduce the environmental impact [91]. Compulsory regulation can set some quality standards to reduce waste [92].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Those biodegradables, you can turn them into fertilizer, Resident G said. According to a study of Jara-Samaniego, et al (2017) [26], composting with gardening pruning wastes have shown their feasibility in terms of matter mineralization and humification where the composts obtained have the suitable characteristics for agricultural use. Furthermore, the composts obtained can be used as an organic fertilizer because they showed absence of phytotoxicity and suitable agronomic properties.…”
Section: Compost Soilmentioning
confidence: 99%